Taking Advantage of the Ambivalent Reactivity of Ynamides in Gold Catalysis: A Rare Case of Alkyne Dimerization - Kramer, Søren; Odabachian, Yann; Overgaard, Jacob; Rottländer, Mario; Gagosz, Fabien; Skrydstrup, Troels (Angewandte Chemie International Edition, 2011)
A gold mine of results: A series of ynamides have been dimerized in the presence of a gold(I) complex. This unprecedented transformation involves the formation of a key keteniminium intermediate that reacts to form a variety of cyclic and acyclic products. The substitution pattern of the ynamide determines which product is formed (see scheme; EWG=electron‐withdrawing group, Ts=p‐toluenesulfonyl).